Can fluorescence confocal microscopy replace frozen sections for margin assessment in Mohs micrographic surgery?. (3rd June 2019) - Notingher, I.
Abstract : Linked Article : Longo et al. Br J Dermatol 2019; 180 :1473–1480 .